Emergence and evolution of an international cluster of MDR Bacteroides fragilis isolates - Sóki József (JOURNAL OF ANTIMICROBIAL CHEMOTHERAPY, 2016)
N2 - Objectives The aim of this study was to examine the antibiotic resistance profiles, antibiotic resistance mechanisms and possible ‘clonal’ nature of some MDR Bacteroides fragilis strains that simultaneously harboured cfiA, nimB, IS1186 and IS4351